Fate of radium on the discharge of oil and gas produced water to the marine environment. (June 2021) - Ahmad, Faraaz; Morris, Katherine; Law, Gareth T.W.; Taylor, Kevin G.; Shaw, Samuel
Abstract: Understanding the speciation and fate of radium during operational discharge from the offshore oil and gas industry into the marine environment is important in assessing its long term environmental impact. In the current work, 226 Ra concentrations in marine sediments contaminated by produced water discharge from a site in the UK were analysed using gamma spectroscopy. Radium was present in field samples (0.1–0.3 Bq g −1 ) within International Atomic Energy Agency activity thresholds and was found to be primarily associated with micron sized radiobarite particles (≤2 μm). Experimental studies of synthetic/field produced water and seawater mixing under laboratory conditions showed that a significant proportion of radium (up to 97%) co-precipitated with barite confirming the radiobarite fate pathway. The results showed that produced water discharge into the marine environment results in the formation of radiobarite particles which incorporate a significant portion of radium and can be deposited in marine sediments. Highlights: Selected field marine sediments in the vicinity of a wastewater discharge site contained elevated levels of Ra and Ba. Ra speciation and fate was determined via heavy liquid extractions, mixing experiments and geochemical modelling. Barite particles isolated from field sediments contained measurable 226 Ra activity confirming the radiobarite fate pathway. Synthetic/field produced waters were mixed with seawaters to successfully mimick the formation of (radio)barite particles. Ra uptake experiments showed Ra primarily exists in the form of radiostrontiobarite following produced water discharge.